Electron–neutral bremsstrahlung radiation fingerprints the initial stage of nanosecond discharge in liquid water. (9th April 2021) - Bílek, Petr; Tungli, Ján; Hoder, Tomáš; Šimek, Milan; Bonaventura, Zdeněk
Abstract: We postulate that basic radiative signatures observed during the initial phases of nanosecond discharge in liquid water can be attributed to the electron–neutral bremsstrahlung process. Principal characteristics of the radiation collected from developing luminous filaments consist of a sharp decrease in the emission intensity at the short-wavelength side of the spectra, followed by a maximum and subsequent decrease in intensity towards near-infrared wavelengths. All these radiative features can be attributed to the electron–neutral bremsstrahlung produced by a bell-like energy distribution of the electrons. Such an electron energy distribution function is coherent with the concept of electric field emission into electrostriction-induced nanovoids. The findings of this work help in elucidating the hitherto unclear mechanism(s) of plasma generation in liquid water.